2017
DOI: 10.1103/physrevd.96.114004
|View full text |Cite
|
Sign up to set email alerts
|

Test of the multiquark structure of a1(1420) in strong two-body decays

Abstract: We present an analysis of strong two-body decays of the a1(1420) with J P C = 1 ++ recently reported by the COMPASS Collaboration at CERN. Following the interpretation of the COMPASS Collaboration that the a1 is an unusual state with a four-quark qqss structure we consider two possible configurations for this state -hadronic molecular and color diquark-antidiquark structures. We find that the dominant decay mode of the a1 is the decay into K and K * . In particular, we calculate that the four decay modes a1 → … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Ref. [168]. The meson a 1 was modeled there as a four-quark state with diquark-antidiquark and molecule structures.…”
Section: The Axial-vector Resonance a 1 (1420)mentioning
confidence: 99%
See 1 more Smart Citation
“…Ref. [168]. The meson a 1 was modeled there as a four-quark state with diquark-antidiquark and molecule structures.…”
Section: The Axial-vector Resonance a 1 (1420)mentioning
confidence: 99%
“…Two-body strong decays of a 1 in the context of the covariant confined quark model were examined in Ref. [168]. The meson a 1 was modeled there as a four-quark state with diquark-antidiquark and molecule structures.…”
Section: The Axial-vector Resonance a 1 (1420)mentioning
confidence: 99%
“…The authors of Ref. [98] studied the two-body decay rates for the modes a 1 ð1420Þ → f 0 ð980Þπ and a 1 ð1420Þ → KK Ã ð892Þ for four-quark configurations using the covariant confined quark model. They found that a molecular configuration is preferred over a compact diquark-antidiquark state.…”
mentioning
confidence: 99%
“…[29]. In this work partial decay channels of a 1 ð1420Þ were investigated in the framework of the covariant confined quark model by treating a 1 ð1420Þ as a tetraquark with both diquark-antidiquark and molecular structures.…”
Section: Introductionmentioning
confidence: 99%